O metodách a cílech terénního výzkumu jazyka a kultury - Zima, Petr (Lidé města, 2001)
1. Although traditionally links between methods of field research of languages and cultures have been emphasised and in the approach of some American descriptive schools the research of language and culture was even made part of a joint methodological framework of anthropology, there are also undoubtedly some basic differences. 2. Biological and cultural criteria are perhaps too much stressed in the question of the choice of the informants in traditional works about the problems of field research; one has to stress here the diversity of the criteria with which informant are selected in the field research of language and culture. While research of culture requires a measure of orientation and experience (which implies a higher age and proportion of the years spent in a given community for the people under examination), good information can also be provided for the research of language also by a psychologically and physically orientated very young man (a student). By contrast, older people under examination dosely linked with a culture and some habits can become under certain circumstances an obstacle to objective research of a neutral register of a given variety/language because instead of it they force field researchers to accept a functionally biased specific register of culturally bound texts (such as oral literature). 3. The choice of the type of texts is also vital: most traditional texts providing relevant information about culture are monologic accounts. A picture arisen from the analysis of such texts does not cover neutral expressions in a given code, especially in the sphere of syntax. From the linguistic viewpoint one has to confront such monologic texts with neutral dialogues on day-to-day themes (which, in their turn, have a smaller value in terms of research of culture). 4. The field research of culture and language cannot be entirely separated in the sphere of analysis in view of their natural communication links. Instead, one always has to bear in mind which priorities within the framework of a given research are really of primary importance and which are only registered for further use by a different discipline.